Patterns of antropyloric motility in fed healthy preterm infants. Issue 2 (1st September 2002) - Hassan, B B; Butler, R; Davidson, G P; Benninga, M; Haslam, R; Barnett, C; Dent, J; Omari, T I
Abstract : Background: Antropyloric motility is important for regulation of gastric emptying and has not been adequately characterised in premature infants. Aim: To evaluate fed patterns of antropyloric motility in premature infants. Subjects: Forty three healthy premature infants, 30–38 weeks of postmenstrual age. Methods: Postprandial antropyloric motility was measured using a micromanometric feeding assembly (outer diameter 1.8 mm) incorporating a pyloric sleeve sensor. The occurrence of isolated pyloric pressure waves (IPPWs) and antral pressure wave sequences (PWSs) was characterised. Sequences were further classified as being antegrade, synchronous, antegrade-synchronous, and retrograde according to the direction of propagation. Results: A total of 7289 pressure wave events were recorded, 48% IPPWs and 52% PWSs (18% antegrade, 12% synchronous, 13% antegrade-synchronous, 2% retrograde, and 7% undefined). IPPWs predominated in the first postprandial hour, peaking at 30–60 minutes. PWSs predominated in the period after one hour postprandially. Mean (SEM) half gastric emptying time was 42 (4) minutes. Conclusions: Monitoring of antropyloric motor patterns in healthy premature infants indicates that the neuroregulatory mechanisms responsible for the coordination of antropyloric motility and gastric emptying are well developed by 30 weeks of postmenstrual age.